LITERATURE REVIEW: TANTANGAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS CLOUD DI ERA DIGITAL (2020–2025) - M. Ramadhani Saputra; Arisky Andrinaldo; Sunika Sunika; Dwi Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This literature review examines the challenges of implementing cloud-based accounting information systems (AIS) in the digital era during 2020–2025. The study systematically analyzes open-access scholarly articles from multiple databases, focusing on technical, organizational, regulatory, security, and external factors that affect cloud accounting adoption. Findings indicate that integration with legacy systems, data security and privacy concerns, limited digital skills among human resources, regulatory differences, and vendor dependency are the main barriers. Despite these challenges, cloud accounting provides significant benefits, including operational cost efficiency, real-time access to data, scalability, and automated integration with business processes. The review highlights the need for strategic change management, proper staff training, and robust security policies to ensure successful implementation. Furthermore, gaps in empirical research, especially in developing countries and long-term effectiveness studies, present opportunities for future research.